2020
DOI: 10.3389/fmolb.2020.599475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Prognostic Value of Tumor Microenvironment-Related Genes in Esophageal Squamous Cell Carcinoma

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is the most prevalent histological type of esophageal cancer, but there is a lack of definite prognostic markers for this cancer.Methods: We used the ESTIMATE algorithm to access the tumor microenvironment (TME) of ESCC cases deposited in the TCGA database, and identified TME-related prognostic genes using Cox regression analysis. A least absolute shrinkage and selector operation or LASSO algorithm was used to identify key prognostic genes. Risk scores were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…MXRA8 is reported to confer debilitating acute and chronic musculoskeletal disease, since it serves as an entry mediator for multiple arthritogenic alphaviruses ( 15 ). In terms of tumor progression, several studies have reported that high expressions of MXRA8 had poor overall survival (OS) in kidney renal clear cell carcinoma patients and is correlated with tumor microenvironment in esophageal squamous cell carcinoma ( 16 ). However, the underlying functions of MXRA8 in gliomas have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…MXRA8 is reported to confer debilitating acute and chronic musculoskeletal disease, since it serves as an entry mediator for multiple arthritogenic alphaviruses ( 15 ). In terms of tumor progression, several studies have reported that high expressions of MXRA8 had poor overall survival (OS) in kidney renal clear cell carcinoma patients and is correlated with tumor microenvironment in esophageal squamous cell carcinoma ( 16 ). However, the underlying functions of MXRA8 in gliomas have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…CELF4, one of the CELF protein family, which belongs to a group of splicing regulators that controls developmentally regulated and tissue-specific splicing events [ 28 ]. SLC24A2, a potassium-dependent sodium-calcium exchanger, were observed in pancreatic ductal adenocarcinoma and were associated with esophageal squamous cell carcinoma prognosis [ 29 ]. TRIM67 was involved in neuroprotective effects and tumor processes, has been reported as a potential target to inhibit CRC metastasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESCC is the prevalent histological subtype of esophageal cancer, with a poor prognosis and prone to distant metastasis [ 3 , 27 ]. Therefore, exploring potential biomarkers is essential for managing and predicting the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%